2006
DOI: 10.1016/j.jinorgbio.2006.06.016
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of myo-inositol hexakisphosphate in the presence of magnesium(II) and calcium(II): Protein-free soluble InsP6 is limited to 49 μM under cytosolic/nuclear conditions

Abstract: Progress in the biology of myo-inositol hexakisphosphate (InsP6) has been delayed by the lack of a quantitative description of its multiple interactions with divalent cations. Our recent initial description of these [J. Torres, S. Dominguez, M.F. Cerda, G. Obal, A. Mederos, R.F. Irvine, A. Diaz, C. Kremer, J. Inorg. Biochem. 99 (2005) 828–840] predicted that under cytosolic/nuclear conditions, protein-free soluble InsP6 occurs as Mg5(H2L), a neutral complex that exists thanks to a significant, but undefined, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
90
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 63 publications
8
90
0
Order By: Relevance
“…In fact, many cellular total InsP 6 measurements revealed values below 50 μ m , but in other cells also higher total concentrations up to 100 μ m were found (Table 2), in particular when correcting for a cytosolic plus nuclear water content of only 70 % of the wet weight of cells (see references in Veiga et al , 2006 3 H] myo-inositol demonstrated that a fraction of InsP 6 comprising > 50 % of the total prelabeled amount is apparently soluble and rapidly released. A smaller fraction effusing slower is a clear indication of limited diffusion or scavenging, respectively, of part of the prelabeled InsP 6 (Stuart et al , 1994 ).…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, many cellular total InsP 6 measurements revealed values below 50 μ m , but in other cells also higher total concentrations up to 100 μ m were found (Table 2), in particular when correcting for a cytosolic plus nuclear water content of only 70 % of the wet weight of cells (see references in Veiga et al , 2006 3 H] myo-inositol demonstrated that a fraction of InsP 6 comprising > 50 % of the total prelabeled amount is apparently soluble and rapidly released. A smaller fraction effusing slower is a clear indication of limited diffusion or scavenging, respectively, of part of the prelabeled InsP 6 (Stuart et al , 1994 ).…”
Section: Future Researchmentioning
confidence: 99%
“…Inside cells (pH 7.0 -7.1), where resting Ca 2 + is below micromolar and cellular Mg 2 + is the prevailing free cation varying between 0.5 and 1.5 m m free concentration, according to the calculations of Kremer and coworkers (Veiga et al , 2006 ), a solubility window of the dominant hydrated (Mg) 5 H 2 InsP 6 complex of up to 49 μ m should exist. In fact, many cellular total InsP 6 measurements revealed values below 50 μ m , but in other cells also higher total concentrations up to 100 μ m were found (Table 2), in particular when correcting for a cytosolic plus nuclear water content of only 70 % of the wet weight of cells (see references in Veiga et al , 2006 3 H] myo-inositol demonstrated that a fraction of InsP 6 comprising > 50 % of the total prelabeled amount is apparently soluble and rapidly released.…”
Section: Future Researchmentioning
confidence: 99%
“…1a) thus having the ability to chelate with minerals (multivalent cations), such as calcium. 23,24 More interestingly, IP6 can bind to some kinds of protein, forming direct and indirect complexes ( Fig. 1b and 1c) 23,28 and has a cross-linking effect on protein nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…In plant cells, InsP 6 (inositol hexakisphosphate) mainly acts as a phosphate source and as a store of multivalent cations, because it binds Mg 2+ , Ca 2+ , Zn 2+ and Fe 3+ with high affinity [1]. Plant seeds express phytases during germination to get access to phosphate and multivalent cations, and mature plants use secreted phytases of rhizosphere bacteria and fungi to dephosphorylate soil InsP 6 [2,3].…”
Section: Introductionmentioning
confidence: 99%